PENGUJIAN IMPAK BESI COR KELABU AUSTEMPER - Wibowo, Dwi Basuki; Purwanto, D (ROTASI, 2007)
Grey cast iron representing Fe-C alloy as steel. Grey cast iron graphite in form of flake. Grey cast iron at most used compared to other casting metals, this matter because of amenity process production, can be made mass productions and cost of process which competing, etc. Though offering many advantage, but there are some lacking of that is mechanical properties do not as high as steel. To improve the mechanical properties, in this research the grey cast iron was austempered. This process is conducted by holding the specimens at austenite temperature ( 850ÂºC) during 1 until 2 hour, then quenched in NaNO2 and KNO3 as cooler media. At the quench process conducted by temperature variations to knowing effect of quench temperature at the austempered. Impact, Hardness and metalographi testing have been conducted to evaluate effect of austempering on the mechanical properties and micro structure of austempered materials. By austempered treatment, will improve strength of impact equal to 5.83 % until 45.01 % at non-alloyed grey cast iron, and 15.74 % until 43.47 % at alloyed-0,3 % Cr grey cast iron. Improved of hardness properties also happened equal to 8.57 % until 37.11 % at non-alloyed grey cast iron, and 0.85 % until 38.66 % at alloyed-0,3 % Cr grey cast iron.